Implementation of dna mitochondrial analysis in rhinoclemmys nasuta (testudines: geoemydidae) (2014)
Rhinoclemmys nasuta (Testudines:Geoemydidae) is considered an almost endemic specie to Colombia and the most primitive species of Rhynoclemmys. However, it is classified data deficient by IUCN because the available information is not enough to make a direct or indirect assessment of its extinction risk. Here, we describe the implementation of the method to analyze the mitochondrial DNA control sequence (mtDNA) of R. nasuta in order to generate tools for future studies in systematics and population conservation. Genomic mtDNA was extracted by salting-out from blood samples from Isla Palma and Playa Chucheros (Bahía Málaga - Colombian Pacific Coast). The polymerase reaction chain (PCR) was performed using a pair of degenerate primers (reported for Chrysemys picta, Testudines:Emydidae) in polyacrylamide gel stained with silver nitrate. Fragments of 800pb were obtained and the sequencing reaction was effective.High homology percentage ( and gt; 92 %) was established between the obtained sequences with mtDNA sequences from two species of Geoemydidae, Sacalia quadriocellata and Cuora aurocapitata which are deposited in the GenBank. This demonstrate an effective sequencing ofthe mtDNA control region of R. nasuta.IMPLEMENTACIÓN DE LA METODOLOGÍA DE ANÁLISIS DE ADN MITOCONDRIAL EN Rhinoclemmys nasuta (TESTUDINES:GEOEMYDIDAE)Rhinoclemmys nasuta (Testudines: Geoemydidae) es considerada una especie casi endémica de Colombia y la más primitiva del género, sin embargo, se encuentra clasificada por la IUCN como deficiente de datos, ya que la información disponible no es suficiente para hacer una evaluación directa o indirecta de su riesgo de extinción. Con el propósito de generar herramientas de análisis poblacional se describe la metodología de secuenciación de la región control del ADN mitocondrial (ADNmt) para el análisis genético de poblaciones de Rhinoclemmys nasuta, que permita establecer bases para futuros estudios evolutivos y de conservación. Se realizó la extracción de ADN genómico por desalamiento (“salting-out”), a muestras sanguíneas procedentes de Isla Palma y Playa Chucheros (Bahía Málaga - Pacífico Colombiano). Se realizó la Reacción en Cadena de la Polimerasa (PCR) utilizando una pareja de cebadores degenerados (reportada para Chrysemys picta Testudines: Emydidae), en gel de poliacrilamida teñido con nitrato de plata. Se obtuvieron fragmentos de 800pb siendo exitosa la reacción de secuenciación de los amplificados. Se estableció un alto porcentaje ( and gt;92 %) de homología entre las secuencias obtenidas con secuencias de ADNmt de dos especies de Geoemydidae, Sacalia quadriocellata y Cuora aurocapitata, que están depositadas en el GeneBank, lo que demuestra una efectiva secuenciación de la región control del ADNmt de R. nasuta.